Milking the MOOCs : Blending it Right for Meaningful Flipped Learning - Chuah, Kee Man (CALM, UNIMAS, 2016)
Massive Open Online Course (MOOC) has undergone tremendous changes within a short period of time. Its vast potentials in transforming learning and even the name itself have been scrutinised and debated by various researchers and educationists, so much so that it has created its own ecology for learning that Decker (2014) coined as “MOOCology”. In its humble yet impactful beginning in 2008, MOOC focused on its massiveness and openness. Massive refers to the capability of allowing thousands of students to enrol while open refers to free and open access to anyone regardless of their prior learning (Decker, 2014). Dave Cormier coined the term MOOC after seeing the success of George Siemens’ and Stephen Downes’ course on Connectivism and Connected Knowledge in 2008, luring 2,300 students who took the course for free (Downes, 2008). However, both Siemen and Downes credited the concept of free open online courses to David Wiley and Alec Couros who developed their wiki-based free courses in 2007. By 2012, various MOOCs mushroomed thanks to the introduction of MIT OpenCourseware, Coursera and edX.